Classification on MEMS accelerometer and device application - Chin, Yong Huan; Jaafar, Haslina; Md Yunus, Nurul Amziah (The Society of Digital Information and Wireless Communications (SDIWC), 2014)
MEMS Sensors are devices used to obtain data from the physical surroundings and convert it into useful electrical signals for interpretation and analysis. Sensors can be classified depending on the physical properties that are measured. Any observable and measurable physical properties can be used as the measure and of a sensor. One of the physical properties that can be used for measurement is the acceleration of an object. This physical property can be measured using an accelerometer. The accelerometer measures the acceleration of an object by utilizing the classical Newtonian Law of Forces where forces of the same magnitude will be generated in the opposite direction of the applied force. This force is normally detected by a movable part in the accelerometer and is translated into electrical signal using various electrical principles for further processing and data extraction.